2010
DOI: 10.4314/acsj.v16i1.54325
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of improved banana varieties in Mozambique

Abstract: Banana (Musa spp.) production in Mozambique is largely confined to the Cavendish variety that is eaten as a dessert. On the other hand, banana is a staple food crop in many countries in sub-Saharan Africa. The introduction of a range of high yielding and disease resistant cooking and dessert varieties in Mozambique could play a potential role in ensuring food security and raising incomes of millions of small scale farmers. In the framework of a USAID-funded project on dissemination and evaluation of improved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 3 publications
2
14
1
Order By: Relevance
“…When their standard Cavendish cultivar, 'Grande Naine' was compared to these two hybrids, and unlike our results where 'Williams' performed well in relation to the hybrids, it produced small bunches (12.6 kg) and had lower productivity (16.4 t/ha/yr). On the other hand, Uazire et al (2008) found their standard, 'Grand Naine', produced large bunches (34.1 kg) and cycled well (63.4 weeks), and was significantly better than FHIA-17 (21.5 kg bunches and 66.3 weeks to bunch emergence).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…When their standard Cavendish cultivar, 'Grande Naine' was compared to these two hybrids, and unlike our results where 'Williams' performed well in relation to the hybrids, it produced small bunches (12.6 kg) and had lower productivity (16.4 t/ha/yr). On the other hand, Uazire et al (2008) found their standard, 'Grand Naine', produced large bunches (34.1 kg) and cycled well (63.4 weeks), and was significantly better than FHIA-17 (21.5 kg bunches and 66.3 weeks to bunch emergence).…”
Section: Discussionmentioning
confidence: 92%
“…Others such as SH-3640.10, or 'High Noon', have recently been shown to have excellent eating qualities and research has shown that a significant population of Australian consumers prefer it over Cavendish and Lady Finger in blind taste tests . Similarly SH-3640 was found to have good post-harvest quality and acceptability in terms of aroma and palatability with consumers in southern Mozambique, whereas less than 50% indicated a preference for FHIA-17, FHIA-21 and FHIA-23 (Uazire et al, 2008). However in Cameroon FHIA-21 and FHIA-17 are preferred (Tenkouano et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…in subsistence circumstances). Nonetheless, their adoption by local producers still depends on local uses and preferences, and hybrids that would be readily accepted in one area might not be used in another (Nowakunda and Tushemereirwe, 2004;Dzomeku et al, 2007;Gaidashova et al, 2008;Njuguna et al, 2008;Uazire et al, 2008). Understanding these requirements is key to the successful deployment of clones that would tolerate TR4.…”
Section: Resistancementioning
confidence: 95%